ALIENATION IN CAPITALIST SOCIETY IN KURT VONNEGUT'S CAT'S CRADLE : An Analysis Of Karl Marx's Theory Of Alienation - Pranasari, Dian (2013)
Entitled Alienation in Capitalist Society in Kurt Vonnegut's Novel Entitled Cat's Cradle (An Analysis by using Karl Marx's Theory of Alienation), the present study analyzes the novel Cat's Cradle by using Karl Marx theory of alienation. The study is aimed to uncover how alienation in capitalist society is reflected in the novel and the effects of alienation on the main characters. The study uses qualitative descriptive method with textual analysis approach. The study finds that as portrayed in Cat's Cradle, in capitalist society everything is appreciated when it is profitable. This paradigm then decisively shapes the way the main characters think and act, and produces a civilization that trapped in alienation. The textual evidence shows that there are three forms of alienation in capitalist society as reflected in Cat's Cradle, which are: religious alienation, technological alienation (commodity fetishism), and economic alienation. The study also finds that in order to overcome alienation, instead of coping with the real distress, the main characters choose to seek solace by practicing egoism or just the opposite, altruism.